AUTONOMOUS TARGET TRACKING FOR AIRSOFT GUN BASED ON LABVIEW VISION 2015 - Syafrizal Syarief; Fhyras Ayatullah Rismawa (Jurnal Poli-Teknologi, 2018)
ABSTRACTAutomatic Target Tracking on Airsoft Gun Based on LabVIEW Vision is a system that serves to track the movement of the target which is the target of the airsoft gun. The target that is being targeted is a shooting target that moves on the X and Y axes.To track the target is done through the mechanism of controlling the angle position in the elevation and azimuth fields using continuous linear control techniques against normal lines X and Y. The angular position in the elevation field is limited to -10 ° to + 10 ° and azimuth -45 ° to + 45 ° with resolution smaller or equal to 0.2 degrees. When the target does not move, the tracking will automatically stop right at the central point of the target, then Airsoft Gun automatically shoots the target, with an effective shooting distance of 1.5 meters.The target position is identified using LabVIEW Vision based color and pattern recognition methods. The Angle Position Control System used is P (Proportional) Control with a value of Kc = 10, Ti = 0, and Td = 1x10-6 with the amount of time to reach the set point (sp) of 4.7 seconds.The percentage error in the position of the angle obtained is 1.38%. The resolution of the angle obtained is 0.08 °. The maximum range of equipment obtained at the angles of -10o and + 10o is -152.24 cm and 152.59 cm. We concluded that the standard deviation value obtained from the calculation of the angle value of the actual distance is 0.8.Keywords: Automatic target, airsoft gun, color and pattern recognition, LabVIEW Vision 2015ABSTRAKPenjejak Target Otomatis pada Airsoft Gun Berbasis LabVIEW Vision adalah suatu sistem yang berfungsi untuk menjejak pergerakan target yang menjadi sasaran tembak dari airsoft gun. Target yang menjadi sasaran tembak berupa sasaran tembak (shooting target) yang bergerak pada sumbu X dan Y.Untuk menjejak target dilakukan melalui mekanisme pengendalian posisi sudut pada bidang elevasi dan azimuth menggunakan teknik kontrol linier kontinyu terhadap garis normal X dan Y. Posisi sudut pada bidang elevasi dibatasi -10° s.d +10°dan bidang azimuth -45° s.d +45° dengan resolusi lebih kecil atau sama dengan 0,2 derajat. Ketika target tidak bergerak, maka secara otomatis penjejakan akan berhenti tepat mengarah ke titik sentral dari target, kemudian Airsoft Gun secara otomatis menembak target tersebut, dengan jarak tembak efektif yaitu 1,5 meter.Posisi target diidentifikasi menggunakan metode pengolahan citra (color and pattern recognition) berbasis LabVIEW Vision. Sistem Kontrol Posisi Sudut yang digunakan adalah Kontrol P (Proportional) dengan nilai Kc=10, Ti=0, dan Td=1x10-6 dengan besar waktu untuk mencapai set point (sp) sebesar 4,7 detik. Persentase error posisi sudut yang diperoleh adalah 1,38%. Besar resolusi sudut yang diperoleh adalah 0.08°. Jangkauan maksimum dari alat yang didapatkan pada sudut -10o dan +10o sebesar -152,24 cm dan 152,59 cm. Nilai standar deviasi yang didapatkan dari perhitungan nilai sudut terhadap jarak sebenarnya adalah 0,8.Kata kunci : Penjejak target otomatis, airsoft gun, color and pattern recognition, LabVIEW Vision 2015